(1217) The meaning of capita- Text of a lecture delivered at a seminar held at I.N.P. Cairo, on 20 December 1977 - Robinson, Joan (The Institute Of National Planning., 2018)
the controversies over so-called capital theory arose out of the search for a model appropriate to a modern western economy, which would allow for an analysis of accumulation and of the distribution of the net product of industry between wages and profits.